The challenges of globalization rethinking nature, culture, and freedom (New York American journal of economics and sociology, 2007)
This volume contains eleven essays dealing with the question of how to face the current challenges of globalization. The essays included in this volume were originally presented at the Renvall Institute for Area and Cultural Studies, University of Helsinki, Finland, on the occasion of the Sixth World Congress of the International Society for Universal Dialogue (ISUD) Presents Keynote addresses or prize?winning papers from the Congress Central theme explores the need to rethink our concepts of nature, culture, and freedom in an age of increased globalization Topics examined range from global justice, international law, and human rights to ecoterrorism, cultural relativism, and the challenges of autonomy Introduced by Steven V. Hicks, past President of the ISUD, who discusses the issues of cultural conflict and crisis in the aftermath of Nietzsche′s philosophy
Papers presented at the 6th World Congress of the International Society for Universal Dialogue, held in Helsinki, 2006.
Keywords: Globalization -Congresses.